CHARACTERISTICS OF APPLICATION OF PRELIMINARY MEASURES IN THE PROCEDURE OF CONFISCATION OF PROPERTY OF ILLICIT ORIGIN - Khachatryan, Meri (State and Law, 2022)
One of the efficient guarantees for the seizure of assets of illicit origin is the implication of effective mechanisms for freezing and securing such assets. In contrast to civil litigation, the procedure of confiscation of property of illicit origin consists of certain successive phases, which are aimed at the examination of the property in question and if there are conditions prescribed by law, at its confiscation. The article discusses the peculiarities of the application of the means of preliminary measures in the confiscation of property of illicit origin. The paper reveals and analyzes its relation with the application of the means of securing the claim. The preconditions are met, in case of which the authorized body is entitled to take action for preliminary measures.The article presents range of issues and guidelines that the court should determine during the examination of the application thereby determining the need and scope of its implication. Taking into consideration that the assets can be frozen for a lengthy period, the assets preservation and management mechanisms during the pre-trial security measures phase have been proposed.